Target capital structure and acquisition choices: Evidence from the Greek market - Vasiliou, Dimitrios; Eriotis, Nikolaos; Daskalakis, Nikolaos (SPOUDAI Journal of Economics and Business, 2008)
The main objective of this paper is to analyze whether deviations from the target capital structure affect firms’ decisions to become acquirers. The analysis is conducted in two stages. In the first stage we estimate the target leverage ratio considering the main determinants of capital structure. In the second stage we examine whether the deviation from the predicted target debt ratio affects acquisition choices. Our data come from 112 Greek companies listed on the Athens Exchange during 1997–2002. Our empirical results justify our hypothesis that the leverage deficit is negatively related to the probability of a firm becoming an acquirer. Thus, underleveraged firms, according to their target capital structure, are more likely to become acquirers than overleveraged firms. We also test whether size and profitability affect acquisition choices and we find that larger firms are more likely to become acquirers, whereas profitability does not seem to play an important role. Results and conclusions are consistent with similar studies conducted for other economies. JEL Classifications: G3, G32